Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Konsumen - Indah Yuliana; Aunur Rofiq; Ami rotil Ummah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
In business development, every business actor must pay attention to the products to be marketed, especially in terms of product quality. It should be noted that improvements in product quality and prices are very important, because they can satisfy consumers with the products they buy. And will influence consumers to buy again and again. This study aims to determine the correlation of product quality and price on consumer purchasing decisions in the Home industry, Rengginang Renggol, Olean Situbondo Village. This study uses a quantitative survey approach or Ex post facto which intends to determine the effect of product quality and price on consumer purchasing decisions. In the course of collecting data, researchers used the method of observation and questionnaires (questionnaire). While the analysis technique uses correlative analysis (causal/cause-effect), which is a relationship or influence that states a cause-and-effect relationship between two or more variables. In this study, the research population refers to the Home industry customers of Rengginang Renggol, totaling 265 customers. The sample taken was 15%, namely 40 respondents using random sampling technique. The data analysis technique used to answer the research hypothesis is statistical analysis with SPSS.16 analysis, Somer's D with Ordinal data type. ) evidenced from 0.820 > 0.05. There is an effect of the price variable (X2) as evidenced from 0.000 <0.05 with a value of 0.840. Keywords: Product Quality, Price, Consumer Purchase Decision